Effect of strength training on functional outcomes and strength in patients with polyneuropathy: A scoping review - Pedersen, Britt Stævnsbo; Kodal, Louise Sloth; Kaalund, Anna Bundgaard; Holm-Yildiz, Sonja; Pedersen, Mette Merete; Dysgaard, Tina (Frontiers in Physiology, 2023)
Introduction: Polyneuropathy (PNP) is a chronic progressive disease that over time can lead to damage of sensory, motor and/or autonomic peripheral nerves. Symptoms vary from predominantly sensory to severe sensorimotor affection both proximally and distally. This can result in considerable functional impairments that affect activities of daily living. In other neurological patients, strength training has shown to improve strength and functional outcomes. Since medical treatment only exists for very few percentages of the underlying causes it is obvious to consider if strength training could be a potential treatment for functional impairments. To date little is known on the effect of strength training in patients with PNP. Aim: The aim of this scoping review was to summarize research on strength training and outcomes on physical function in patients with PNP. Methods: We systematically searched five data bases; Pubmed, Embase, Cinahl, Cochrane library and Web of science. Studies on strength training (load ≥70% of 1RM) in patients with PNP were included. The search was carried out in November 2022. Results: 362 articles were screened by title and abstract, 101 articles were full text screened. Eight studies were included. Patients with Charcot-Marie-Tooth (CMT), chronic inflammatory polyneuropathy (CIDP) and diabetic peripheral neuropathy (DPN) were represented in the studies (five RCTs, two case-series, and one cross-over trial). The methodological quality ranged from fair-poor in seven studies, one study reached good quality. Results from the studies indicated that strength training in CMT, CIDP and DPN may improve strength. However various outcomes were used to evaluate strength training, so direct comparisons were difficult. Discussion: In this scoping review we summarized research on strength training and outcomes evaluated in the interventions in patients with PNP. Eight studies were included, they indicated that strength training may be beneficial for patients with PNP. However, due to low methodological strength of most studies a recommendation for patients with PNP cannot be made. Thus, the low number of studies with relative low quality where various functional outcomes were used underscores the importance of future studies to evaluate the effect of strength training on relevant functional outcomes and strength in patients with PNP.